Perinatal Outcome of Preterm Infants <1500 g after IVF pregnancies compared with natural conception. Issue 3 (5th May 2010) - Messerschmidt, A; Olischar, M; Birnbacher, R; Weber, M; Pollak, A; Leitich, H
Abstract : Objective: In vitro fertilisation (IVF) pregnancies are at increased risk for adverse perinatal outcome including very low birth weight infants. The purpose of this study was to find out whether the perinatal outcome of preterm infants <1500 g after IVF is different from those in naturally conceived pregnancies. Patients and methods: This retrospective cohort study included preterm infants <1500 g born between 1999 and 2007 in a tertiary perinatal referral centre. All analyses were made separately for singletons and multiples, divided into infants <1000 g and 1000–1499 g. The primary study outcomes were infant mortality, short term pulmonary morbidity and cerebral morbidity. The secondary study outcomes were small for gestational age, Apgar score at 5 min, the results of the first venous blood gas analysis of the preterm infant, and the first mean arterial blood pressure after neonatal intensive care unit admission. Logistic regression analysis was done to assess the impact of IVF compared to other maternal and infant factors. Results: 1423 patients (195 IVF and 1228 non-IVF patients) were included in this study. The incidence of preterm labour was significantly higher in multiples after IVF than in spontaneously conceived multiples. In the IVF group, there were significantly more multiples. Mortality, pulmonary morbidity and cerebral morbidity did not differ among patients after IVF and naturally conceived patients. Also, there were no significant differences for the secondary outcomes, except for a significantly higher initial pH value in multiples after IVF between 1000–1499 g. Conclusion: IVF treatment was not associated with adverse outcome in very low birth weight infants. IVF, preterm birth, VLBW, singletons, multiples, outcome